Of Holocausts and Gun Control - Daniel D. Polsby; Don B. Kates Jr. (Washington University Law Quarterly, 1997)
This Article seeks to reclaim a serious argument from the lunatic fringe. We argue a connection exists between the restrictiveness of a country's civilian weapons policy and its liability to commit genocide upon its own people. This notion has received a good deal of disdainful public attention over the past several years because of the Oklahoma City bombing, the "Republic of Texas" siege, and the inflamed subculture from which the defendants in those incidents emerged. We argue that there is a great deal more to weapons policy than some sort of cost-benefit calculation of firearms' crime control benefits versus public health costs. The larger point, that no one who has lived through the greater part of the twentieth century may conscientiously disregard, is that sometimes people in power behave like Stalin, Hitler, Pol Pot, or Mao Zedong rather than like President Clinton. Of course public policy must acknowledge that exceptional brutality is indeed exceptional rather than commonplace. But it is senseless to pretend that what has happened many times before cannot possibly happen again. Sound policy makes allowances for even remote contingencies when they are grave enough, and denies opportunity to predators whenever it can.
Keywords: Gun control; Genocide